ACCEPTANCE OF COOKIES SUBSTITUTE OF MILLET FLOUR AND BRAN FLOUR AS PROTEIN ENERGY SOURCES - Ilmi Anugriani; Abdul Salam; Safrullah Amir; Nurhaedar Jafar; Nurzakiah (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2022)
ABSTRACT Introduction: One of the government's efforts in addressing the problem of underweight in Indonesia is PMT (Supplementary Feeding). As an effort to support government programs, innovations of nutritious and locally substituted PMT are needed. Cookies made from millet and bran can be used as a source of protein-energy for underweight toddlers. Objective: This study aims to determine the production process, quality, and acceptability of the formulation of cookies substituted with millet flour and bran flour. Materials and Methods: The type of this study is descriptive observational. 15 formula cookies were tested through hedonic quality test on 15 trained panelists and also hedonic test on 15 semi-trained panelists. Data processing and analysis were carried out using SPSS with the Kruskall Wallis test, the data were presented in the form of images, tables, and narratives. Result: The process of making cookies is preparing tools and materials, mixing ingredients, weighing and printing dough, baking and cooling. The results of the hedonic quality test on trained panelists were that there were significant differences in the parameters of color, texture, taste and overall with sig. <0.05. The highest overall hedonic quality was found in the F15 formula which was in the good category. In semi-trained panelists, the highest level of preference was found in the F15 formula. Conclusion: Cookies substituted with millet flour and bran have a significant effect on the hedonic quality parameters of color, texture, and taste. Overall, the panelists chose formula 15 as the most preferred formula and rated it good compared to other formulas. It is recommended that this product of millet flour and bran substitution cookies be developed further and pay attention to the use of an oven that has a fixed measuring device in the manufacturing process. Keywords : Millet, Rice Bran, Cookies, Acceptance